On the treatment of persons with disabilities in organizations: A review and research agenda - Beatty, Joy E.; Baldridge, David C.; Boehm, Stephan A.; Kulkarni, Mukta; Colella, Adrienne J. (Human Resource Management, 2019)
Human resource practitioners play a crucial role in promoting equitable treatment of persons with disabilities, and practitioner's decisions should be guided by solid evidence‐based research. We offer a systematic review of the empirical research on the treatment of persons with disabilities in organizations, using Stone and Colella's seminal theoretical model of the factors influencing the treatment of persons with disabilities in work organizations, to ask: What does the available research reveal about workplace treatment of persons with disabilities, and what remains understudied? Our review of 88 empirical studies from management, rehabilitation, psychology, and sociology research highlights seven gaps and limitations in extant research: (a) implicit definitions of workplace treatment; (b) neglect of national context variation; (c) missing differentiation between disability populations; (d) overreliance on available data sets; (e) predominance of single‐source, cross‐sectional data; (f) neglect of individual differences and identities in the presence of disability; and (g) lack of specificity on underlying stigma processes. To support the development of more inclusive workplaces, we recommend increased research collaborations between human resource researchers and practitioners on the study of specific disabilities and contexts, and efforts to define and expand notions of treatment to capture more nuanced outcomes.